2002
DOI: 10.1055/s-2002-25088
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Primary Obstructed Megaureter (POM) and Indication for Operative Treatment

Abstract: Presented is the diagnostic and therapeutic management of the primary obstructed megaureter (POM). 42 patients presented with 53 ureteral units (UU) of POM (5 females, 37 males, 36 neonates and 6 children aged 3 to 8 years). Of the 53 megaureters 10 UU (19%) were on the right and 27 UU(51 %)were on the left. 8 patients (19%)with 16 UU (30%)showed a bilateral abnormality. In 41% of the patients, hydronephrosis had been discovered by prenatal ultrasound. All patients were evaluated postnatally by ultrasound (US)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 8 publications
0
19
0
2
Order By: Relevance
“…Tc-MAG3 with furosemide (10,31). This estimate of absolute renal function has been used to differentiate obstructive dilatations with implications for the renal parenchyma from those without.…”
Section: Discussionmentioning
confidence: 99%
“…Tc-MAG3 with furosemide (10,31). This estimate of absolute renal function has been used to differentiate obstructive dilatations with implications for the renal parenchyma from those without.…”
Section: Discussionmentioning
confidence: 99%
“…Although diuresis renogram is widely regarded as the most useful tool for assessing the degree of obstruction, there is little exact data [6,15,25] and the prognosis of intermediate obstruction (O'Reilly type D) is unclear. We found a very similar risk of later deterioration and surgery, as well as of spontaneous regression, in patients with initially intermediate obstruction and those with relevant obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical therapy was performed in most cases. With modern ultrasound techniques, about 40% of POMs are discovered prenatally [6] and the fraction of symptomatic children decreased to 22-50% [7,8]. In the 1990s, several reports documented the high rate of spontaneous regression of prenatally diagnosed POM [7,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…According to today's knowledge that a high percentage of the primary obstructive megaureters normalizes without impairment of renal function, the conservative approach is justified in severe asymptomatic cases too [1,3,15,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…A spontaneous improvement rate of 43% to 100 % (median 90) of the unoperated patients was registered. In studies which refer exclusively to asymptomatic pre-and/ or directly post-natally diagnosed megaureters, the rate of the children operated on is only between 0 and 28% [3,8,[19][20][21]. A long-time follow-up revealed that the performance of the kidneys with a primary megaureter produced the expected growth during the organ maturation in case of conservative treatment [5].…”
Section: Discussionmentioning
confidence: 99%